Asked by nkrbasak | 22nd Sep, 2010, 03:31: PM
Let R be the rows and N be the number of students in a row. Then number of students, NR.
(N + 3) then R - 1,
(N - 3) then R + 2,
But (N + 3)(R - 1) = Total number of students = NR
3R - N = 3 ... (1),
(N - 3)(R + 2) = NR, and this gives,
-3R + 2N = 6 ... (2)
Adding (1) and (2),
N = 9 and hence R = 4.
Total number of students, 9x4 = 36.
Answered by | 22nd Sep, 2010, 04:37: PM
Kindly Sign up for a personalised experience
- Ask Study Doubts
- Sample Papers
- Past Year Papers
- Textbook Solutions
Verify mobile number
Enter the OTP sent to your number